Comunidades de macroinvertebrados de solo respondem à restauração e à fertilidade do solo de florestas ripárias? - Pestana, Luís Fernando de Abreu (Universidade Federal de São Carlos, 2019)
Tropical riparian zones, considered essential due to their high ecological value for water quality, soil stabilization and biodiversity conservation, are an example of areas that are intensively degraded by agricultural activities. Ecological restoration, which leads to intervention procedures of degraded environments aiming at the reestablishment of their ecosystem functions, is one of the existing mechanisms to minimize the anthropic effects of degradation. For the success of restoration, one of the essential factors is soil quality, which maintains the plant and animal productivity of an ecosystem. To evaluate these conditions, soil macroinvertebrates are important indicators of the conditions of an ecosystem, since they vary with changes in soil and vegetation quality. However, there are few studies that consider these organisms in restoration areas, also considering soil conditions. We evaluated in this study whether the structure and composition of the soil macroinvertebrate communities respond to the restoration gradient in which they are located, as well as to the nutrient availability of the substrate. The study was conducted in a riparian area inserted in an agricultural context. The diversity and composition of soil macroinvertebrates were evaluated in three adjacent vegetation types characterized by being at different stages of succession - pasture, restoration area and remnant forest fragment. The area under restoration was managed through the reintroduction of ten tree species native to the region five years ago, a project implanted in an area formerly used as pasture. In addition, the area encompassing the three vegetation types is on a longitudinal gradient of soil fertility. The variables of environmental characterization of the area (vegetation structure and soil chemistry) were obtained. The macrofauna was obtained by the pitfall method and identified at the morphospecies level. Indicators of the structure of the soil macroinvertebrate communities responded differently to the environmental conditions. Abundance and richness, although indicating differences between vegetation types, evidencing higher values in the restoration, followed by pasture and forest, when used alone may not provide important information on the factors that determine the structure of macroinvertebrate communities that inhabit the litter, since the diversity, dominance and fairness indexes showed that soil quality also positively influences communities, with greater diversity and uniformity in environments with greater availability of nutrients. Thus, indices that consider relative abundance combined with wealth indexes seem to be more effective. Simplified and restoration environments have a positive effect on nutrients by increasing plant productivity, increasing the availability of resources and habitats, which reflects increasing the diversity and uniformity of communities. Regarding the composition of the communities, 3 factors are decisive for their structuring: The type of vegetation existing; the availability of nutrients, which affects productivity; and the presence of grasses. Communities of restoration areas with nutrient inputs and low percentage of grasses indicate an approximation with remnant forest communities
Soil macroinvertebrate communities respond to restoration and soil fertility of riparian forests?
Keywords: Disponibilidade de nutrientes; Estrutura de vegetação; Macroinvertebrados de solo; Restauração ecológica; Ecological restoration; Nutrient availability; Soil macroinvertebrates; Vegetation structure; CIENCIAS BIOLOGICAS::ECOLOGIA